Novel approaches to the treatment of Pseudomonas aeruginosa infections in cystic fibrosis - Hurley, M.N.; Cámara, Miguel; Smyth, Alan R. (European Respiratory Society, 2012)
Pseudomonas aeruginosa chronically infects patients with cystic fibrosis and is associated with greater morbidity. There has been limited progress on the clinical development of new antibiotics with novel modes of action. This review addresses some of the latest research developments on the exploitation of candidate adjuvant therapeutic agents that may act alongside conventional antibiotics as an alternative therapeutic strategy. After considering key mechanisms this opportunistic pathogen employs to control virulence, the progress of various strategies including the inhibition of quorum sensing, efflux pumps and lectins, and the use of iron chelators, bacteriophages, immunisation and immunotherapy is reviewed. Both therapeutic approaches in early development and clinical phase are discussed.